SUPLEMENTASI SERBUK GERGAJI DENGAN PROBIOTIK UNTUK PAKAN KELINCI - Nonok Supartini; Harimurti Februari Trisiwi (BUANA SAINS, 2016)
This study has aims for : (1) knowing the superiority usage of sawdust as the supplementation of rabbit feed. (2). Knowing the factors effected to the degree of the usage sawdust efficiency as rabbit feed supplementation. (3) knowing the degree of feed convertion and feed cost per gain of sawdust fermentation usage as rabbit feed suplementation. By this study, it expected can be : (1) information for rabbit breeder as an alternative feed as sawdust concentrate which can improve the carcass production and anality. (2) the cheap alternative feed for substituting the expensive one.This study has done at husbandry laboratory of Universitas Tribhuwana Tunggadewi Malang. It used 20 local rabbits at the age of 6 months with the weight average 1,2 to 1,5 kg. This study used experiment methods which designed by Complete Random Design (RAL) consists of 4 treatments repeated for 5 times, and there is 4 rabbitd each experiment.The treatments have given are: P0. Fresh vegetable feed + conevntional concentrate; P1: fresh vegetable feed + 2% fermentation sawdust (from fresh vegetable feed); P2: fresh vegetable feed + 4% fermentation sawdust added (from fresh vegetable feed); P3: fresh vegetable feed + 6% fermentation sawdust (from fresh vegetable feed). The variables have been observed are feed consumption, feedd convertion dail weight addition and FCG (Feed Cost per Gain) and IOFC (Income Over Feed Cost).According to this study, it can be concluded that the usage of sawdust increases weight, dry matter consumption, feed costs, and decrease feed cost pr gain and FCR. The usage of 2% fermentation sawddust supplementation gave best results for all variables.It is suggested to use 2% fermentation sawdust supplementation from forage rabbit in order to increase the feed and decrease feed cost per gain.